Sorption and preconcentration of metal ions on silica gel modified with 2,5-dimercapto-1,3,4-thiadiazole - Lessi, P.; Dias, N. L.; Moreira, J. C.; Campos, JTS (Elsevier B.V., 1996)
Silica gel, chemically modified with 2,5-dimercapto-1,3,4-thiadiazole [=Si(CH2)(3)-NC2HNS3], abbreviated as SiB, was used to adsorb metal ions from ethanol by both batch and column techniques. Elution of Cu(II) was done with a solvent mixture of acetone and hydrochloric acid (9:1 v/v). Zn(II), Cd(II), Ni(II), Pb(II), Co(II) and Fe(III) were eluted with 0.5 mol l(-1) HC1 in ethanol solution. The modified silica was applied in the preconcentration of metal ions from commercial ethanol, normally used as engine fuel. The method is suitable for quantifying these metals at low mu g l(-1) levels.
Keywords: preconcentration; silica gel functionalized; 2,5-dimercapto-1,3,4-thiadiazole; bismuthol I